Dye Adsorption Mechanism of Glass Fiber-Reinforced Plastic/Clay Ceramics and Influencing Factors - Hiroyuki Kinoshita (Polymers, 2021)
The effective reuse of waste glass fiber-reinforced plastic (GFRP) is desired. We previously produced porous ceramics by firing mixtures of crushed GFRP and clay in a reducing atmosphere and demonstrated their applicability as adsorbents for the removal of basic dyes from dyeing wastewater. However, the primary influencing factors and the dye adsorption mechanism have not been fully elucidated, and the adsorption of acidic and direct dyes has not been clarified. In this study, adsorption tests were conducted, and the effects of the firing atmosphere, specific surface area, type of dye, and individual components were comprehensively investigated. The results showed that reductively fired ceramics containing plastic carbide residue adsorbed basic dye very well but did not adsorb acidic dye well. The clay structure was the primary factor for the dye adsorption rather than the GFRP carbide. The mechanism for the basic dye adsorption appears to have been an increase in specific surface area due to the plastic carbide residue in the ceramic structure, which increased the ion exchange between the clay minerals and the dye. By adjusting the pH of the aqueous solution, the GFRP/clay ceramic also adsorbed considerable amounts of direct dye, so the mechanism was determined to be ion exchange with the calcium component of the glass fibers.